Alveolar bone regeneration potential of a traditional Chinese medicine, Bu‐Shen‐Gu‐Chi‐Wan, in experimental periodontitis. (27th August 2013) - Yang, H.; Wen, Q.; Xue, J.; Ding, Y.
<x xml:space="preserve">Abstract</x> Background and Objective The aim of this study was to investigate the effect of a traditional Chinese medicine, Bu‐Shen‐Gu‐Chi‐Wan, on experimental periodontitis and bone regeneration in rat. Material and Methods Sixty female Sprague‐Dawley rats were divided equally into three groups: a healthy control group (Group N); a periodontitis group (Group P); and the Bu‐Shen‐Gu‐Chi‐Wan treatment group (Group T). A 0.2‐mm wire was placed around the maxillary first molar and Porphyromonas gingivalis was injected into the gingival sulcus. Rats in different groups were administered 0.9% normal saline or Bu‐Shen‐Gu‐Chi‐Wan solution (4 g/kg of body weight, for three alternate days), and the animals were killed after 4 wk. Morphological analysis of alveolar bone rebuilding was performed using micro‐computed tomography (micro‐CT) and stereomicroscopy, and the variation of inflammation in the periodontium was determined histologically. The serum levels of the proinflammatory cytokines interleukin‐1beta (IL‐1β) and tumor necrosis factor‐alpha (TNF‐α) and of the bone‐turnover biomarkers pyridinoline cross‐linked carboxyterminal telopeptide of type I collagen (ICTP) and osteocalcin (OC) were determined using radioimmunoassays. Results After treatment with Bu‐Shen‐Gu‐Chi‐Wan, there were significant decreases in the levels of IL‐1β, TNF‐α, ICTP and OC and decreased inflammatory infiltration in the periodontal tissues of Group T. significant changes in alveolar bone volume and density were detected by micro‐CT, but stereomicroscopy did not detect a significant improvement of alveolar bone height. Conclusion The data of the present study suggest that the traditional Chinese medicine, Bu‐Shen‐Gu‐Chi‐Wan, has anti‐inflammatory function in experimental periodontitis and may simultaneously improve alveolar bone remodeling.